Joint Land Certification and Intra-household Decision-making:Towards Empowerment of Wives? - Stein Holden; Sosina Bezu (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2013)
We have used gender-disaggregated household panel data from 2007 and 2012 in combination with dictator games and hawk-dove games to assess the effects of joint land certification of husbands and wives on wives' involvement in land-related decisions within households. Wives' stated preferences for stronger land rights to women and husbands' stated preferences for the traditional weak position of women were significantly affecting the wives' degree of within household involvement in land-related decisions in opposite directions. Within-household generosity as expressed in dictator game experiments between husbands and wives, was correlated with stronger involvement of wives in land-related decisions.
Keywords: D03; J16; Q15; 330; Joint land certification; gender; empowerment of wives; experiments; Ethiopia